Purkinje Cell Signaling Deficits in Animal Models of Ataxia - Hoxha, Eriola; Balbo, Ilaria; Miniaci, Maria Concetta; Tempia, Filippo (Frontiers in Synaptic Neuroscience, 2018)
Purkinje cell dysfunction or degeneration is the most frequent finding in animal models with ataxic symptoms. Mutations affecting intrinsic membrane properties can lead to ataxia by altering the firing rate of Purkinje cells or their firing pattern. However, the relationship between specific firing alterations and motor symptoms is not yet clear, and in some cases Purkinje cell dysfunction precedes the onset of ataxic signs. Moreover, a great variety of ionic and synaptic mechanisms can affect Purkinje cell signaling, resulting in different features of motor dysfunction. Mutations affecting Na+ channels (NaV1.1, NaV1.6, NaVβ4, Fgf14 or Rer1) reduce the firing rate of PCs, mainly via an impairment of the Na+ resurgent current. Mutations that reduce Kv3 currents limit the firing rate frequency range. Mutations of Kv1 channels act mainly on inhibitory interneurons, generating excessive GABAergic signaling onto PCs, resulting in episodic ataxia. Kv4.3 mutations are responsible for a complex syndrome with several neurologic dysfunctions including ataxia. Mutations of either Cav or BK channels have similar consequences, consisting in a disruption of the firing pattern of PCs, with loss of precision, leading to ataxia. Another category of pathogenic mechanisms of ataxia regards alterations of synaptic signals arriving at the Purkinje cell. At the parallel fiber-Purkinje cell synapse, mutations of GluD2 or its ligand Crbl1 are responsible for the loss of synaptic contacts, abolishment of long-term depression and motor deficits. At the same synapse, a correct function of mGlu1 receptors is necessary to avoid ataxia. Failure of climbing fiber maturation and establishment of Purkinje cell mono-innervation occurs in a great number of mutant mice, including mGlu1 and its transduction pathway, GluD2, semaphorins and their receptors. All these models have in common the alteration of Purkinje cell output signals, due to a variety of mechanisms affecting incoming synaptic signals or the way they are processed by the repertoire of ionic channels responsible for intrinsic membrane properties. Although the Purkinje cell is a final common pathway of ataxia, the link between specific firing alterations and neurologic symptoms has not yet been systematically studied and the alterations of the cerebellar contribution to motor signals are still unknown.